1999
DOI: 10.1121/1.426902
|View full text |Cite
|
Sign up to set email alerts
|

Influences of pellet markers on speech production behavior: Acoustical and perceptual measures

Abstract: Peri- and intraoral devices are often used to obtain measurements concerning articulator motions and placements. Surprisingly, there are few formal evaluations of the potential influence of these devices on speech production behavior. In particular, the potential effects of lingual pellets or coils used in x-ray or electromagnetic studies of tongue motion have never been evaluated formally, even though a large x-ray database exists and electromagnetic systems are commercially available. The x-ray microbeam dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 41 publications
2
34
1
Order By: Relevance
“…Prior to the experiment, each subject participated in a three-minute training session (on how to use the SSI), which also helped them adapt to the oral sensors. Previous studies have shown those sensors do not significantly affect their speech output after a short practice (Katz et al, 2006;Weismer and Bunton, 1999).…”
Section: Setupmentioning
confidence: 99%
“…Prior to the experiment, each subject participated in a three-minute training session (on how to use the SSI), which also helped them adapt to the oral sensors. Previous studies have shown those sensors do not significantly affect their speech output after a short practice (Katz et al, 2006;Weismer and Bunton, 1999).…”
Section: Setupmentioning
confidence: 99%
“…These audio signals were digitised at a rate of 20 kHz, using 16 bits of quantisation. Measures employed previously in articulatory perturbation studies were used to determine the effect of the artificial palate upon speech production [17,19] . The measures included were as follows:…”
Section: Acoustic Analysismentioning
confidence: 99%
“…The listeners were asked to complete a rating of the speech stimuli using a procedure similar to that of Weismer and Bunton [17] . The raters were instructed 'You will hear a series of repetitions of the phrase, say __ again ; please listen carefully and decide if you think the speaker is wearing an artificial palate or not, then place a tick in the appropriate column (yes/no) beside the phrase number'.…”
Section: Perceptual Analysismentioning
confidence: 99%
See 2 more Smart Citations